364 AlloDerm with Duragen Underlay for Duraplasty in Chiari Malformation Result in Excellent Outcomes. (1st April 2022) - Eli, Ilyas; Hamrick, Forrest; Kim, Robert; Schmidt, Richard
Abstract : INTRODUCTION: Numerous tissue grafts are available for posterior fossa dural augmentation after Chiari decompression surgery. The outcomes for preventing postoperative pseudomeningocele and csf leak formation vary, but no consensus exists for the graft material with lowest complication rates. Use of Alloderm has been shown to have superior outcomes with a 2.2% rate of causing pseudomeniogcele requiring reoperation. METHODS: A retrospective single institution cohort included 106 patients who underwent Chiari decompression surgery by a single surgeon from 2014 through 2021. Age, sex, BMI, tonsillar descent, syrinx formation, type of dural graft used, and follow up data were analyzed with univariate statistical tests and Chi-squared test. RESULTS: A retrospective single institution cohort included 106 patients who underwent Chiari decompression surgery by a single surgeon from 2014 through 2021. Age, sex, BMI, tonsillar descent, syrinx formation, type of dural graft used, and follow up data were analyzed with univariate statistical tests and Chi-squared test. CONCLUSION: The use of the AlloDerm dural graft with Durgen underlay for duraplasty in Chiari decompressions resulted in similar pseudomeningocele formation rate when compared with the use of Alloderm alone. However, the use of Alloderrm with Duragen underlay results in a significantly lower rate for need for reoperation. There was no association between patient age, sex, BMI, on the need for reoperation.